Teachers' perceived knowledge, attitudes, and readiness to implement MTSS for students with disabilities in Saudi Arabia - Alsudairy, Nouf Abdullah; Alkeraida, Ali; Alhilfi, Reem Abdullah; Eltantawy, Mahmoud Mohamed (Frontiers in Education, 2025)
BackgroundEffective implementation of the Multi-Tiered System of Supports (MTSS) depends largely on teachers' knowledge, attitudes and preparedness. This study assesses teachers' perceived knowledge, attitudes, and readiness to implement the MTSS for students with disabilities.MethodThis study employed a cross-sectional descriptive survey design using descriptive analysis. Data were collected from 413 teachers from kindergarten, elementary, intermediate, and secondary mainstream schools across Riyadh, Saudi Arabia who were recruited using the simple random sampling method.ResultThe findings revealed that teachers have a high level of knowledge of (M = 3.95, SD = 0.679), a positive attitude toward (M =3.93, SD= 0.717), and a strong readiness to (M =4.08, SD = 0.709) implement MTSS.ConclusionThe findings highlight the need for ongoing professional development to translate teachers' positive perceptions into effective MTSS practices. Future research should examine how these factors translate into practices. The application of qualitative methods would provide deeper insights into how teachers apply MTSS in practice.